Kir6.2 mutations causing neonatal diabetes provide new insights into Kir6.2-SUR1 interactions. - Tammaro, P; Girard, C; Molnes, J; Njølstad, P; Ashcroft, F (2005)
ATP-sensitive K(+) (K(ATP)) channels, comprised of pore-forming Kir6.2 and regulatory SUR1 subunits, play a critical role in regulating insulin secretion. Binding of ATP to Kir6.2 inhibits, whereas interaction of MgATP with SUR1 activates, K(ATP) channels. We tested the functional effects of two Kir6.2 mutations (Y330C, F333I) that cause permanent neonatal diabetes mellitus, by heterologous expression in Xenopus oocytes. Both mutations reduced ATP inhibition and increased whole-cell currents, which in pancreatic beta-cells is expected to reduce insulin secretion and precipitate diabetes. The Y330C mutation reduced ATP inhibition both directly, by impairing ATP binding (and/or transduction), and indirectly, by stabilizing the intrinsic open state of the channel. The F333I mutation altered ATP binding/transduction directly. Both mutations also altered Kir6.2/SUR1 interactions, enhancing the stimulatory effect of MgATP (which is mediated via SUR1). This effect was particularly dramatic for the Kir6.2-F333I mutation, and was abolished by SUR1 mutations that prevent MgATP binding/hydrolysis. Further analysis of F333I heterozygous channels indicated that at least three SUR1 must bind/hydrolyse MgATP to open the mutant K(ATP) channel.